A geochemical study of bitumen residues on ceramics excavated from Early Bronze age graves (3000–2900 BCE) at Başur Höyük in SE Turkey. (January 2018) - Connan, Jacques; Kavak, Orhan; Sağlamtimur, Haluk; Engel, Michael; Zumberge, Alex; Zumberge, John
Highlights: Black spots on ceramics from graves at Başur Höyük (SE Turkey) are bitumen residues. The source of bitumen was not identified. Bitumen occurrence is a consequence of the human activity during the mortuary ceremony. Abstract: Eight black residues, scraped from outer surfaces of painted ceramics, unearthed from graves 1–3 at Başur Höyük (SE Turkey), were analysed by geochemical techniques in order to characterize bitumens and to try to identify their source. Ceramics are dated from the Early Bronze period (3100–2900 BCE). The black organic matter was indeed identified as bitumen, but its source has not been discovered despite its comparison with several oil seeps from the area. The bitumen at Başur Höyük does not match the bitumens analyzed at Kavuşan Höyük, Salat Höyük, Hakemi Use and Kuriki Höyük which are Cretaceous in origin and likely imported from the Eruh tars deposit. The stable carbon isotope values of their asphaltene fraction suggest a Silurian origin, however the occurrence of the 18α(H)-oleanane emphasized a younger source, i.e. Tertiary or Cretaceous. Our interpretation favours the mixture of two oils, a Silurian age and a Tertiary-Cretaceous age. This mixture may occur geologically, due to the uptake of a Tertiary signal by a Silurian oil along its migration route to the surface. It may also be a consequence of human activity carried out by the inhabitants at the mortuary ceremony where the bituminous mixture has been applied to ceramics, prior to their deposit in the graves. The oil seep character of the archaeological bitumen at Başur Höyük and the lack of obvious oxidation suggest the following explanation: freshly collected oil seeps were splashed on ceramics as ritual practices and the tarry potteries were then buried and therefore sealed. The fast burial prevented the bitumen from any oxidative alteration.